Barriers to rural women’s participation in social insurance for farmers, villagers, and nomads: the case of Iran - Ghadermarzi, Hamed (Frontiers in Sociology, 2024)
IntroductionSince the enactment of the Law of Comprehensive Structure for Social Welfare and Security in Iran, only a small fraction of its target has been accomplished and a significant part of rural women have not been covered by the social insurance service yet. A few studies have been conducted on the social insurance of rural people. However, no study has ever addressed the issue of women with a focus on the theoretical aspects of sociology science, which is the contribution of the present research. Therefore, the present research aimed to explore the barriers to rural women’s participation in social insurance.MethodsThe research adopted a qualitative approach and the grounded theory method. It was conducted among the brokers of social insurance for farmers, villagers, and nomads in Iran. Data were collected through interviews.Results and DiscussionThe results showed that the barriers to women’s participation in social insurance were economic (e.g., women’s economic dependence on the family head), social (e.g., low social trust, low literacy and awareness of rural women, and limitations imposed by religious doctrine), cultural (e.g., limited social communications, limited use of technology, and poor insurance culture), legal (e.g., poor legal support for rural women’s insurance and non-satisfaction of expectations from the fund services), and institutional (e.g., inefficient advertisement methods and poor awareness-raising measures).